Computer-Based System For Calibration Of Temperature Transmitter Using Rtd - Mohd Syakirin, Ramli; Najidah, Hambali; Mohd Ashraf, Ahmad; Shahrizal, Saat (2010)
Using the temperature calibration instrument, the purpose of this paper is to design the uncertainty calculation system. The test was conducted using Resistance Temperature Detector (RTD) sensor, transmitter, and repeated for three times. The data acquisition (DAQ) card is used to interface the temperature instrument and the computer. In order to determine the uncertainty of the temperature measurement, graphical user interface (GUI) software has been developed in Visual Basic(VB) programming language. The developed software shows that the uncertainty of the temperature transmitter measurement can be calculated by interfacing the instrument to the computer through DAQ card. The study focuses on manual temperature measurement and concentrates only on RTD temperature sensor. The results provide the confidence limits of five-point calibration of temperature transmitter that could improve the teaching techniques using computer-based system of the temperature measurement.